Pastoralne aspekty odnowy w Duchu Świętym - Biela, Bogdan (Śląskie Studia Historyczno-Teologiczne, 1998)
Thirty years have passed when once again in the Catholic Church we are enjoying the revival of the charismatic movement called the „Renewal in the Holy Spirit”. This movement, although it arises controversy and insinuations, still lasts, continues to develop and is sweeping with its range over millions of Christians all over the world. In 1975 Paul VI said that it was the chance for the Church of today and for the world. The article presenting the essence of the Renewal, its fruit and the dangers involved points to certain conditions that must be fulfilled in order to take advantage of this chance. In the face of diminishing religious practice, and at the same time of the trend to satisfy the hunger for religious experience through completely false ways, the Renewal in the Holy Spirit appears to be a sign of hope, because what forms its essence is not a system or method, but above all the experience of God’s reality, His Goodness and power. This is the source of the widely understood religious and moral changes that transform the life of its members. Of course, certain negative aspects also occur, however, they can be avoided by suitable management and subordination to priestly authority. The basic pillar of the Renewal is formed by the communities. They are the ones that help in acquiring special dispositions that condition God’s action in man. There arises, in this connection a demand for their proper management and for a suitable formation of secular animators. Also a very important thing for the future of the Renewal is the attitude of priests themselves, who on account of their vocation have a unique and irreplacable role to be played, first of all in its integration with the life of the Church. There would be something abnormal about it, if the Renewal by strengthening the life of the Church remained without their commital, as this after all, could be the cause of its dwindling and also lead to various distortions. It has become visible that traditional forms of ministry, basing on the postTridentine model of the parish are less and less effective. To start with, the Renewal in the Holy Spirit by „increasing the value” of the sacrament of Holy Baptism and Confirmation, can contribute considerably to the revival of the parish, as it is impossible to simply „introduce” enlivening of the parish. A personal meeting with Jesus Christ in the power of His Spirit must always be the point of departure. On this foundation developing communities can through their missionary ways, reach people who do not have any contact with the Church anymore. There also appears the need to integrate in common action the Renewal in the Holy Spirit with our own native Movement of Light-Life which has already developed an overall and realistic program of parish animation.